Distributional consequences of labor demand adjustments to a downturn: A model-based approach with application to Germany 2008-09 - Olivier Bargain; Herwig Immervoll; Andreas Peichl; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2010)
Macro-level changes can have substantial effects on the distribution of resources at the household level. While it is possible to speculate about which groups are likely to be hardesthit, detailed distributional studies are still largely backward-looking. This paper suggests a straightforward approach to gauge the distributional and fiscal implications of large output changes at an early stage. We illustrate the method with an evaluation of the impact of the 2008-2009 crisis in Germany. We take as a starting point a very detailed administrative matched employer-employee dataset to estimate labor demand and predict the effects of output shocks at a disaggregated level. The predicted employment effects are then transposed to household-level microdata, in order to analyze the incidence of rising unemployment and reduced working hours on poverty and inequality. We focus on two alternative scenarios of the labor demand adjustment process, one based on reductions in hours (intensive margin) and close to the German experience, and the other assuming extensive margin adjustments that take place through layoffs (close to the US situation). Our results suggest that the distributional and fiscal consequences are less severe when labor demand reacts along the intensive margin.
Keywords: D58; J23; H24; H60; 330; labor demand; tax-benefit system; crisis; income distribution; Konjunktur; Wirtschaftskrise; Arbeitsnachfrage; Schock; Verteilungswirkung; Arbeitszeitflexibilisierung; Lohnersatzleistungen; Beschäftigungseffekt; Deutschland